Treatment-seeking threshold and accessibility of psychiatric outpatient services in Switzerland: the relationship with stigma and self-esteem - Billian, Janina; Imfeld, Lukas; Roth, Carl B.; Moeller, Julian; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2024)
Perceived stigmatization and low self-esteem are linked to poorer mental health outcomes, but their impact on treatment-seeking thresholds and the importance of outpatient service location remain unclear. The study included 525 outpatients of the University Psychiatric Clinic (UPK) Basel, Switzerland, of whom 346 were treated at inner city services and 179 at services located on the main site of the UPK at the outer city limits. Perceived discrimination and devaluation (PDD), self-esteem (SE), treatment-seeking threshold (TST), and accessibility were measured via a self-reported questionnaire. The PDD consisted of 12 items evaluating beliefs about the level of stigma towards individuals with mental illness in the general population on a 5-point Likert scale. SE, TST and accessibility were assessed through single-item 7-point Likert scales. PDD and SE were positively correlated (p < 0.001), suggesting that lower perceived stigma was linked to higher self-esteem, and were not associated with TST. The relationship between PDD and SE remained consistent after controlling for age, gender, and nationality. Age was negatively correlated with TST (p = 0.022), while gender did not significantly influence any of the variables. There was little variation regarding PDD, with emergencies at the site of the psychiatric clinic and substance use disorder (SUD) patients reporting higher levels of stigmatization. Emergency patients and those with SUD and personality disorder reported the lowest SE ratings. TST showed a broad range and was highest for emergency services and transcultural psychiatry patients. Differences in accessibility were mainly linked to the location, with outpatient service users in the inner city reporting better accessibility (p < 0.001) and higher SE (p = 0.009). In comparison to patients using services with planned contacts only, patients in emergency settings differed by higher TST (p = 0.018) and better ratings of accessibility (p = 0.004). In conclusion, there was a relevant amount of stigmatization, impaired self-esteem, and, for some outpatient services, high thresholds to seek treatment. Future research should explore other factors influencing TST. The findings highlight the need to address stigmatization and accessibility when planning mental health services.